Analysis of the Juvenile Idiopathic Arthritis Immunization Schedule - L. S. Namazova-Baranova; S. I. Valieva; M. V. Fedoseenko; D. A. Novikova; N. E. Tkachenko; A. G. Gaivoronskaya; M. I. Broeva; T. A. Kaljuzhnaya; F. Ch. Shakhtakhtinskaya; E. I. Alekseeva; K. B. Isaeva (Педиатрическая фармакология)
Background: The connection between vaccination and autoimmune diseases (and rheumatic pathology in particular) is still a subject of discussions. When discussing the possibility of vaccinating rheumatic patients we should take into account the ultra high dangers that infectious diseases pose for such patients, including those that can be prevented by vaccination. We should also take into account the experience of using various vaccine types in rheumatic patients, which illustrates of their high safety profile.Objective: Our aim was to study the immunization schedule in children with juvenile idiopathic arthritis.Methods: The evaluation of vaccine history and other anamnestic data in juvenile idiopathic arthritis patients was based on individual medical records (individual child’s card/preventive vaccination certificate), as well as questionnaires filled by mothers.Results: It has been determined that a significant proportion of children with vaccination schedule deviations are juvenile idiopathic arthritis patients. Almost one in four children with a confirmed rheumatic diagnosis has not been immunized against the major vaccine-preventable diseases. In one non-vaccinated group, there was a case of juvenile arthritis onset after recovering from measles. A small number of patient mothers connects the manifestation of rheumatic diseases with vaccination.Conclusion: Violations of vaccination status in JIA patients require corrections according to the results of clinical studies and the recommendations of international experts.